Breed Determination for Indonesian Local Chickens Based on Matrilineal Evolution Analysis - Ulfah, Maria; Perwitasari, Dyah; Jakaria; Muladno; Farajallah , Achmad (International Journal of Poultry Science, 2015)
Assessing the molecular characteristic of chickens is the powerful method to differentiate chicken breeds. This study analyses the matrilineal evolution of the Indonesian local chickens based on mitochondrial DNA D-loop region to reveal their genetic diversity and phylogenetic relationships. The estimated genetic diversity of Indonesian local chickens ranged from 0.00171 to 0.01800. Six (6) groups from 67 D-loop haplotypes of Indonesian chickens are observed in this study. The Indonesian local chickens can be differentiated from Saudi Arabian, ornamental and commercial line chickens. However, maintaining genetic variation of certain chicken population will be useful to conserve local genes for future utilization.